Versatility of the pinwheel flap to reconstruct circular defects in the temporal and scalp region. Issue 2 (April 2013) - Simsek, Tekin; Eroglu, Lutfi
Abstract The pinwheel flap technique involves raising four small rotation flaps, which are 90° apart from each other and converge into a defect in their centre. It is suitable for resurfacing defects of the scalp, which offers limited skin mobility. It may also be used for certain circular skin defects on the hairless temporal region. This study first re-formularised the original description of this flap technique via a laboratory study. Thanks to a new smaller flap design, closure was achieved with a lesser scar. Afterwards, the technique was used on the 14 patients who had circular skin defects of the temple and scalp. Defect diameters and resultant scar lengths were recorded. When the new design was used, scarring required for defect closure was less than half of that required for the original design. Thus, it was easier to avoid distortion to the anatomical subunits such as eyebrows and hairline. It is believed that this technique is quite appropriate for closing circular defects of scalp up to 50 mm, and temporal defects up to 40 mm. Also, Z-plasties can be added to the design when needed to increase flap rotation and decrease skin distortion.